Dari Genangan Ke Tindakan: Sinergi Lintas Sektor Menangani Banjir Dan Kerusakan Jalan di Pringsewu - Sendgi Intan Syafani; Imelia Putri; Dahlia Dahlia; Riyadillah Agma; Hafis Haliyansyah (Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Mulawarman, 2025)
Purpose: This study aims to analyze the relationship between floods and road damage in Pringsewu Regency and propose a collaborative risk-based management approach. Design/Methodology/Approach: A mixed-methods approach was used, integrating GIS spatial analysis, secondary data from PUPR and BPBD, and semi-structured interviews with 20 youth involved in community initiatives. Findings/Results: Approximately 62.99% (386.93 km²) of Pringsewu is highly flood-prone due to low terrain slope (0–8%) and 1,500–2,000 mm/year rainfall. Over 40% of the 689.5 km road infrastructure is damaged, increasing traffic accidents by 25% over three years. Community initiatives like @seputarpringsewu address temporary repairs but reflect distrust in bureaucracy. Research Limitations/Implications: Limited access to real-time budget data and long-term flood impact records. Practical Implications: Collaborative policies can reduce emergency repairs and enhance infrastructure resilience. Social Implications: Strengthened community participation fosters trust and local empowerment. Originality/Value: This study integrates spatial analysis with community-driven solutions, offering a novel framework for cross-sector disaster management.